Drying shrinkage and moisture loss of lightweight concrete mixed with fine recycled concrete aggregate (FRCA) - Ibrahim, Norisham; Rasli, Izzah Inshirah; Mohd Fauz, Mohd Afiq; Sulong, Zubaidah (Faculty of Civil Engineering, 2025)
The paper reports on drying shrinkage and moisture loss of lightweight concrete exposed to the natural laboratory environment. Concrete was designed using fine recycled concrete aggregate, sand, cement, silica fume, foaming agent and water. Four mixed designs were utilized. The quantity of silica fume used to replace cement was about 10% (by weight of cement). Meanwhile, fine recycled concrete aggregate (FRCA) was used to replace sand from 0% to 30% by weight of sand. Three specimens (300mm x 75mm x 75mm) were cast for each mix and cured for one day. Specimens were measured for shrinkage and moisture loss. The duration of the test was 28 days. Findings from this study show that all the lightweight foam concrete used in this study shrinks in a fluctuating trend when exposed to a natural laboratory environment. The concrete mixed with 20% and 30% of FRCA had the highest and lowest shrinkage values at 28 days, respectively. For every concrete mix, the trend of moisture loss is quite consistent. The concrete with 20% FRCA experienced the largest percentage of moisture loss, which supports the cause of the highest shrinkage strain. Conversely, concrete containing 30% FRCA exhibits the best link between drying shrinkage and moisture loss.